Design of a Rule-Based CIS to Determine the Customer Status of Bank Sumut Binjai - Rahma, Anisa Sri; Rahma, Najahaura; Putri, Raissa Amanda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The development of information technology is driving the banking sector to shift from manual systems to digital systems to improve efficiency, accuracy, and consistency in credit management. This digital transformation has become a crucial need due to the increasing number of customers and the complexity of the credit assessment process that must be carried out by banking institutions. PT. Bank Sumut Binjai Branch still applies manual determination of customer credit status, which has the potential to cause process delays, assessment errors, and inconsistencies in decision-making. This condition can impact the quality of service and credit risk faced by the bank. This study aims to design a Rule-Based Credit Information System that is able to determine customer credit status automatically based on predetermined rules. This system is designed to be able to process customer data systematically according to applicable criteria. The method used is a Rule-Based System which includes the stages of knowledge acquisition, knowledge representation, application of inference engines, and system evaluation. Data collection was carried out through interviews with credit officers and relevant literature studies as a basis for compiling system rules. The system design is modeled using Unified Modeling Language (UML) which is represented through Use Case Diagrams to illustrate the interaction between users and the system. The designed system is expected to assist credit officers in determining customer status quickly, accurately, objectively, and consistently, as well as increase the effectiveness of the credit decision-making process at PT. Bank Sumut Binjai Branch.